2015
DOI: 10.1007/s00436-015-4659-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes or microvesicles? Two kinds of extracellular vesicles with different routes to modify protozoan-host cell interaction

Abstract: Parasite-host cell interaction can be modulated by a dynamic communication between extracellular vesicles (EVs). They should play key roles in cell-cell communications transferring biomolecules (miRNA, proteins, soluble factors) from one cell to another cell. While many names have been used to denominate EVs, a better comprehension to understand these vesicles is raised when we classify it according to biogenesis: originated from multivesicular bodies, named exosomes, and from plasmatic membranes, denominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 49 publications
(50 reference statements)
3
31
0
Order By: Relevance
“…The size of the MVs produced by NK cells of the NK-92 cell line ranged from 210-490 nm, and the peak of the MV quantity distribution was 315 nm. These data complied with our previous work [35] and that of other research groups that ascertained the size of MVs produced by various cells [20,71,75]. The reproducibility of the MV granulometric analysis results obtained in our laboratory at different times has led us to recommend laser correlation analysis as a standard for assessing the isolation purity of these extracellular objects.…”
Section: Laser Correlation Analysissupporting
confidence: 89%
“…The size of the MVs produced by NK cells of the NK-92 cell line ranged from 210-490 nm, and the peak of the MV quantity distribution was 315 nm. These data complied with our previous work [35] and that of other research groups that ascertained the size of MVs produced by various cells [20,71,75]. The reproducibility of the MV granulometric analysis results obtained in our laboratory at different times has led us to recommend laser correlation analysis as a standard for assessing the isolation purity of these extracellular objects.…”
Section: Laser Correlation Analysissupporting
confidence: 89%
“…Proteins important for trypomastigote recognition and infection such as surface glycoprotein Tc‐85 and trans ‐sialidase (TS) were detected on MVs from TCT and META interaction with THP‐1 cells (Tables S2, S3, and S5b,c), which may contribute for parasite infectivity (Reviewed by Maeda, Cortez, & Yoshida, ; Yoshida & Cortez, ). In this way, MVs could function as signals that are internalized by host cells even before contact with the parasite as previously proposed by different groups (reviewed in Torrecilhas et al, ; Marcilla et al, ; Evans‐Osses et al, ). In response, changes in host cell metabolism could facilitate the infection by the parasite.…”
Section: Resultsmentioning
confidence: 63%
“…Over the years, several reports have shown the ability of different protozoan parasites to release EVs that strongly interact with host cells both in vitro and in vivo , resulting in mostly negative modulation or suppression of immune responses to the pathogen (reviewed in Torrecilhas, Schumacher, Alves, & Colli, ; Mantel & Marti, ; Marcilla et al, ; Twu & Johnson, ; Campos et al, ; Coakley, Maizels, & Buck, ; Evans‐Osses, Reichembach, & Ramirez, ). For instance, Trocoli Torrecilhas et al () have demonstrated that EVs from Trypanosoma cruzi infective mammalian tissue culture‐derived trypomastigote (TCT) stage could augment parasite infection of heart tissue, leading to increased animal lethality due to a deleterious inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. elegans , EVs transferred between worms contribute to the specification of male sexual behavior (Wang et al, 2014), while functional EV-associated transcripts encoding a Cre recombinase are shuttled across distant tumors in mice (Zomer et al, 2015). Transfers of EVs and delivery of molecular cargo from human to mouse cultured cells and from the protozoan pathogen Trypanosoma cruzi to human erythrocytes have been documented, suggesting that EVs can indeed serve as widespread mediators of interspecies RNA transfers (Valadi et al, 2007; Deolindo et al, 2013; Evans-Osses et al, 2015). …”
Section: Contrasting and “Ev Sceptic” Perspectivesmentioning
confidence: 99%